Individual and Socio-Cultural Factors as Driving Forces of the Purchase Intention for Organic Food by Middle Class Consumers in Indonesia. Issue 3 (27th May 2022) - Najib, Mukhamad; Sumarwan, Ujang; Septiani, Stevia; Waibel, Hermann; Suhartanto, Dwi; Fahma, Farah
Abstract: The growth of the organic food market attracts more and more attention from researchers and agribusiness entrepreneurs. This paper identifies the role of personal, social, cultural and psychological factors as driving forces for the intention to purchase organic food by middle income class consumers. Data was collected from 527 respondents. A Structural Equation Modeling (SEM) approach was used in the analysis. The results show that social, cultural, personal and psychological factors significantly influence consumer's attitude toward organic food. Moreover, the intention of middle class consumers to purchase organic food is positively affected by attitudes. The results of this study provide an important contribution to marketing scholars and practitioners as well as policy makers, particularly to improve organic food consumption in the context of middle class consumer in emerging market.